2021
DOI: 10.1136/bmjresp-2021-001077
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of as-needed albuterol/budesonide versus albuterol in adults and children aged ≥4 years with moderate-to-severe asthma: rationale and design of the randomised, double-blind, active-controlled MANDALA study

Abstract: IntroductionUncontrolled asthma is associated with substantial morbidity. While fast-acting bronchodilators provide quick relief from asthma symptoms, their use as rescue fails to address the underlying inflammation. Combining a short-acting beta2-agonist, such as albuterol (salbutamol), with an inhaled corticosteroid, such as budesonide, in a single inhaler as rescue therapy could help control both bronchoconstriction and inflammation, and reduce the risk of asthma exacerbations.Methods and analysisThe Phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
6
0
5
Order By: Relevance
“…The study will recruit 1000 patients per treatment group for adults/adolescents and 50 patients per treatment group for patients aged 4-11 years. This study, if successful, will confirm salbutamol/budesonide pMDI as a rescue therapy irrespective of background asthma therapy [32]. The CARE study will be a 52-week phase III RCT on children aged 5 to 15 years with mild asthma treated either with budesonide-formoterol or salbutamol.…”
Section: Pico Question 1 In Children With Infrequent Symptoms Is Saba...mentioning
confidence: 80%
“…The study will recruit 1000 patients per treatment group for adults/adolescents and 50 patients per treatment group for patients aged 4-11 years. This study, if successful, will confirm salbutamol/budesonide pMDI as a rescue therapy irrespective of background asthma therapy [32]. The CARE study will be a 52-week phase III RCT on children aged 5 to 15 years with mild asthma treated either with budesonide-formoterol or salbutamol.…”
Section: Pico Question 1 In Children With Infrequent Symptoms Is Saba...mentioning
confidence: 80%
“…The MANDALA study demonstrating that salbutamol/budesonide can help control bronchoconstriction and slow airway inflammation. 24 A randomized controlled trial showed the use of ICS plus β 2 receptor agonists to reduce persistent cough after lobectomy. 12 The potential mechanism may be the comprehensive anti-inflammatory effect of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ICS alone cannot modify the decrease in FEV1. 17,18 In patients with moderate-severe COPD, the combination of ICS with LABA is more effective in improving lung function, health status and reducing exacerbations. In addition, treatment with LABA/ICS fixed dose combination (FDC) has a significant effect compared to LABA alone, in patients with exacerbations a maximum of once a year.…”
Section: Discussionmentioning
confidence: 99%